2020
DOI: 10.25259/cytojournal_4_2020
|View full text |Cite
|
Sign up to set email alerts
|

Grading of pancreatic neuroendocrine tumors on endoscopic ultrasound-guided fine-needle aspiration using Ki-67 index and 2017 World Health Organization criteria: An analysis of 32 cases

Abstract: Objectives: Biological behavior of pancreatic neuroendocrine tumors (Pan NETs) is difficult to predict on morphology alone. The assessment of proliferation by the Ki-67 proliferation index (PI) is considered to be an important prognostic parameter in these tumors and has been endorsed by the 2017 World Health Organization (WHO) grading system for Pan NETs. Although widely accepted on surgical specimens, there is varied opinion on grading of these tumors on cytology samples. This study aimed at classification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Over the last two decades, the incidence of PNETs has increased due to improved diagnostic techniques, while the mortality has decreased due to the progress in understanding the pathophysiology and natural history of PNETs as well as better treatment and management [3]. Although PNETs are considered long-term indolent tumors, the outcomes of patients with PNETs are highly variable because of their high genetic heterogeneity [4], tissue histological differentiation, Ki-67 proliferation index, and tumor stage [5]. Thus, a personalized management strategy for PNET patients is urgently needed along with a relevant statistical predictive model [6].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, the incidence of PNETs has increased due to improved diagnostic techniques, while the mortality has decreased due to the progress in understanding the pathophysiology and natural history of PNETs as well as better treatment and management [3]. Although PNETs are considered long-term indolent tumors, the outcomes of patients with PNETs are highly variable because of their high genetic heterogeneity [4], tissue histological differentiation, Ki-67 proliferation index, and tumor stage [5]. Thus, a personalized management strategy for PNET patients is urgently needed along with a relevant statistical predictive model [6].…”
Section: Introductionmentioning
confidence: 99%
“…Stratified analysis for tumors ≤ 2 cm was also performed; of the 22 articles, 10 reports showed the individual size or details of the classification ≤ 2 cm. Pooling the data of the studies, the concordance rate was 77.5% and the kappa correlation index was 0.65 (95% confidence interval (CI) = 0.59-0.71, p < 0.01) (Table 3) [55,[61][62][63][67][68][69][70][72][73][74][75][76][77][78][79][80][81][82][83][84]87]. The sensitivity of G1 was good at 91.4% (338/370), but it was poor in G2 and G3 at 55.7% and 59.5%, respectively.…”
Section: Grading Diagnosismentioning
confidence: 97%
“…FNA, fine-needle aspiration; FNB, fine-needle biopsy. Concordance of PNEN grading between EUS-FNAB specimens and surgical specimens in pooling data[55,[61][62][63][67][68][69][70][72][73][74][75][76][77][78][79][80][81][82][83][84]87]. Concordance of PNEN grading between EUS-FNAB specimens and surgical specimens in pooling data with small tumor sizes (2 cm or less)[55,61,62,67,69,73,[75][76][77]81,84].…”
mentioning
confidence: 99%
“…However, it is almost impossible to count in 50 HPFs with FNA samples, and the Ki-67 proliferation index is usually used in clinical practice. The concordance rate of the Ki-67 index between PNENs measured from EUS-FNA samples and surgical specimens was reported to be 54%-100% [37,[43][44][45][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] (Table 1), whereas a systematic review reported a rate of 83% [68]. Pooling the data of the studies which compared the Ki-67 LI grades obtained both in EUS-FNA samples and surgical specimen, the concordance rate was 77.5% and the kappa correlation index was 0.65 (95% confidence interval = 0.59 -0.71, P < 0.01) ( Table 2) [37,[43][44][45][49][50][51][52][54][55][56][57][58][59][60][61][62][63][64]…”
Section: Grading Diagnosismentioning
confidence: 99%
“…Table 2. Concordance of PNEN grading between EUS-FNAB specimens and surgical specimens in pooling data [37,[43][44][45][49][50][51][52][54][55][56][57][58][59][60][61][62][63][64][65][66]69]. Grade 1 Grade 2 Grade 3 Total Grade 1 338 88 5 431 Grade 2 32 111 12 155 Grade 3 0 0 23 23 Total 370 199 40 609…”
Section: Grading Diagnosismentioning
confidence: 99%